2022
DOI: 10.1002/mabi.202100413
|View full text |Cite
|
Sign up to set email alerts
|

Alginate/Gelatin‐Based Hydrogel with Soy Protein/Peptide Powder for 3D Printing Tissue‐Engineering Scaffolds to Promote Angiogenesis

Abstract: In recent years, 3D bioprinting has attracted broad research interest in biomedical engineering and clinical applications. However, there are two issues need to be solved urgently at present, the development of ink is the first pressing thing for 3D printing tissue engineering scaffold, other thing is the promotion of angiogenesis in the scaffold. Therefore, a gelatin/sodium alginate‐based hydrogel with protein‐rich is developed here, which is prepared by gelatin, sodium alginate, and soy protein/soy peptide p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 55 publications
(55 reference statements)
0
17
0
Order By: Relevance
“…An increase in swelling behavior was observed in the presence of PH-containing scaffolds compared with the pure 6-Alg/4-Gel scaffold (Figure S9). This was due to the soluble and hydrophilic components of the hydrolysates contributing to the overall swelling of the scaffolds …”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…An increase in swelling behavior was observed in the presence of PH-containing scaffolds compared with the pure 6-Alg/4-Gel scaffold (Figure S9). This was due to the soluble and hydrophilic components of the hydrolysates contributing to the overall swelling of the scaffolds …”
Section: Resultsmentioning
confidence: 85%
“…Interestingly, a broad peak around 3265 cm −1 (−OH/−NH 2 ) in Alg/Gel was slightly shifted to the higher region (amide-X), indicating the interaction of PHs and IHs with Alg/Gel, as reported earlier. 44,45 Because the hydrolysates were small peptide fragments, the low-temperature gelation of Alg/Gel induced physical cross-linking of hydrolysates inside the polymer matrix. The printed scaffolds were cross-linked with 100 mM CaCl 2 for 30 min at RT.…”
Section: Characterization Of Protein Hydrolysatesmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the effects of SP, Maebuchi measured changes in serum concentrations of various amino acids, finding that SP was consumed faster and more efficiently in humans than protein or amino acid mixtures. [42,43] Many recent studies have shown that SP not only can stimulate tissue growth without the need for growth factors, but also have active fragments with functional properties, such as antioxidant, immunomodulatory, and antiinflammatory activities. [44][45][46][47][48] Therefore, it is assumed that the addition of SP in the patch can provide nutrition, promote wound healing, and reduce postoperative risk.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, angiogenesis is a key process for the repair and regeneration of damaged tissues, and angiogenesis of tissueengineering scaffold is also one of the great challenges for large-volume construction. [30] Recently, many strategies have been reported to solve this issue, such as construction of pre-vascularized channel within scaffolds [31][32][33][34] or using angiogenesis agents to spontaneously form endothelial cell vascular networks, [35][36][37][38] where angiogenesis agents exhibited greater potential in self-promote vascularization of tissue-engineering scaffold. [39] For many years, researchers have discovered that the angiogenic properties of conventional angiogenesis agents (e.g., growth factors) are primarily dependent on reactive oxygen species (ROS).…”
Section: Introductionmentioning
confidence: 99%